TEM-processed defect densities in single-layer TMDCs and their substrate-dependent signature in PL and Raman spectroscopy - Moses Badlyan, Narine; Quincke, Moritz; Kaiser, Ute; Maultzsch, Janina (Nanotechnology, 2024)
The optical properties of the direct-bandgap transition metal dichalcogenides (TMDCs) MoS2 and WS2 are heavily influenced by their atomic defect structure and substrate interaction. In this work we use low-voltage chromatic and spherical aberration (CC/CS)-corrected high-resolution transmission electron microscopy to simultaneously create and image chalcogen vacancies in TMDCs. However, correlating the defect structure, produced and analyzed using transmission electron microscopy (TEM), with optical spectroscopy often presents challenges because of very different fields of view and sample platforms involved. Here we employ a reverse transfer technique to transfer electron-irradiated single-layer MoS2 and WS2 from the TEM grid to various substrates for subsequent optical examination. The dynamics of defect creation are studied in atomic resolution on a separate sample, which allows to apply the derived statistics to larger irradiated areas on the other samples. The intensity of both the defect-bound exciton peak in photoluminescence (PL) and the defect-induced LA(M) mode in Raman spectra increase with defect density. The best substrates for defect-density determination by optical spectroscopy are polystyrene for PL and SiC and Si/SiO2 for Raman spectroscopy. These investigations represent an important step towards the quantification of defects using solely optical spectroscopy, paving the way for fast, reliable, and automatable optical quality control of optoelectronic devices.
CRIS-Team Scopus Importer:2024-08-16
Keywords: defects; HRTEM; MoS; Photoluminescence; Raman; sulfur vacancies; WS